¿Es posible repetir las votaciones parlamentarias?. ¿Vota el diputado o el grupo parlamentario?: a propósito de la STC 361/2006 - García-Escudero Márquez, Piedad (Teoría y Realidad Constitucional, 2007)
The Constitutional Court, through its ruling 361/2006 on an appeal for the protection of constitutional rights (recurso de amparo), tried a case made against a resolution of the Speaker of the Basque Parliament denying the repetition a vote, resulting in the enactment of the 2005 Regional Budget. The ruling raised two questions: the Speaker’s duties in relation to the member’s behaviour when casting their vote in Parliament and the competency to appeal invested on the spokesperson of the parliamentary group to which the plaintiff member belonged. This comment examines the problems involved in parliamentary votes and disagrees, much in the same line as the Constitutional Court’s minority view, with the reasoning of the ruling, insofar as it establishes the Speaker’s duty to prove the member’s negligence when the validity of a vote is in doubt. The author also disagrees with the parliamentary group’s right to collectively reject an initiative, on the grounds that the Constitution enshrines the vote of the parliamentarians as personal and unbounded. This comment also points out other issues left unmentioned by the ruling, like the inability to appeal to the Bureau of the House against the Speaker’s decisions relating to the conduct of the debates and the problem-prone execution of rulings once the legislature has expired, which makes these judgements merely declaratory.